Association of Venous Malformation of the Head and Neck with Meningoencephalocele: Report of 3 Cases - Salehian, S. (AJNR Am J Neuroradiol, 2011)
Venous malformations have previously been reported to be associated with skeletal changes in humans, typically demineralization and localized deformation of the long bones. We report a presumed developmental association between venous malformations of the head and neck and meningoencephaloceles involving the sphenoid and temporal bones. Recognition of this association is important to avoid misinterpretation of these changes as a more aggressive process. We present the imaging findings and suggest an embryologic basis for this previously unreported association.